The Server Provisioning Problem for Continuous Distributed Interactive Applications - Zheng, Hanying (2017)
In this paper, we study the server provisioning problem for continuous Distributed Interactive Applications (DIAs) whose application states not only change because of the operations performed by participants, but also evolve along with the passing of time. We focus on finding the locations of servers for hosting continuous DIAs, with the goals of optimizing the interactivity performance while fulfilling the consistency and fairness requirements. We show that the server provisioning problem is challenging by presenting its NP-hardness and non-approximability results under several conditions. We propose two efficient server placement algorithms and analyze their approximation ratios. The approximation ratio of the proposed M-BETTER algorithm is quite close to a lower bound for any polynomial-time algorithm. We also conduct experimental evaluations to compare the proposed algorithms with several baseline server placements.